Ciliados indicadores de calidad de agua en la Laguna San Miguel del Monte - Zaleski, M. (2000)
The saprobic system is the most widely spread method for the detemination of water quality in freshwater environments. It is based in the presence of organisms which indicate the degree of mineralization of the organic matter in the system, besides dissolved oxygen concentration, biochemical oxygen demand and bacteria abundance, among other parameters. Ciliates are frequently used in this system because an important number of species are excellent indicators. In this paper, ciliate fauna from a section of the San Miguel del Monte pond, related to the Las Perdices pond during periods of flood, is analyzed through bimonthly sampling in the March 1998-March 1999 period. Through the comection of both aquatic bodies, the San Miguel del Monte pond can receive extra organic matter, contributing to the deterioration of its water quality. The majority of species found throughout the year indicate a and B mesosaprobic conditions (high organic matter concentration, large numbers of bacteria and posible oxygen deficit during the night). Most ciliates found feed on bacteria. High bacteria concentrations produce the predominance of such species, opposite to those with other feeding habits. The saprobic condition of this pond indicates for certain periods of the year, an important degree of vulnerability, for which the entrance of organic matter should be restricted or banned